Load shedding scheme based on frequency and ranked stability index considering optimal selectivity of load in islanded distribution system / Norazliani Md Sapari - Norazliani , Md Sapari (2018)
The widespread use of renewable energy sources as Distributed Generations (DGs) in distribution system causes few technical concerns. One of the major concerns is the possibility of islanding occurrences, where the grid is disconnected from the distribution system. When islanding occurs, the system frequency and voltage are severely disturbed due to imbalance between power generation and load demands. Due to this, the DGs are required to be disconnected to avoid system instability and safety issues. However, in the long run, this action is not a wise approach since DGs may able to energize some of the loads in the system. In order to allow DGs to continue operating in islanding mode, imbalance between power generation and load demands must be addressed. One of the possible solutions is to apply load shedding scheme where some loads in the system are disconnected to balance the power between generation and load demands. This scheme has been widely applied in the transmission system, which proven able to stabilize the system frequency. However, islanded distribution network is not as stable as in transmission system that supported with many generations. Thus, a new load shedding scheme is required to ensure frequency and voltage is preserved when load shedding mode takes place. Due to the importance of load shedding for the islanded distribution system, this research aims to propose a new load shedding scheme considering frequency and Voltage Stability (VS). To achieve this, VS index and optimal selectivity of load to be shed are incorporated in the proposed load shedding scheme. A ranking algorithm referred as Bus Ranked Voltage Stability (BRVS) is proposed where the bus (according VS value) is sorted according to the stability value of the bus, from the weakest to the strongest. The weakest bus indicates the critical bus, which is near to collapse point in the system. Based on the BRVS, the weakest bus is given priority to be shed during system disturbances. The proposed scheme also considered the optimal load to be shed based on the VS index and power imbalance criteria. In order to consider both criteria in a balance manner, Analytical Hierarchy Process (AHP) method is adopted. The effectiveness of the proposed scheme is validated through simulation by using PSCAD/EMTDC software. An existing Malaysian network (25 bus system) interconnected with mini hydro generations is used for the test of the proposed scheme. The simulation results show that the proposed scheme managed to shed the optimal amount of load when compared to Conventional and Adaptive Under Frequency Load Shedding Scheme. Apart from frequency stability, the proposed scheme also shows significant improvement in the voltage profile in the islanded system. Moreover, it has been observed that the proposed scheme successfully improves the performance of voltage magnitude in more than 90% from all buses in the system.